Прикраси із мушель у вбранні ранньосередньовічних слов’ян - Володарець-Урбанович, Я.В. (Археологія і давня історія України, 2021)
У статті розглянуто знахідки мушель, виявлених у складі кількох дніпровських скарбів першої й другої хронологічних груп за О. О. Щегловою, інгумації з речами кола «старожитностей антів» та на поселенні празької культури. Низка таких прикрас виявлена і на роменських пам’ятках. Проаналізовано шляхи появи підвісок із мушель і варіанти їх використання у вбранні слов’ян. The pendant from Luka-Kavetchyna, dwelling 25 (fig. 2: 1; 3) is the earliest find from the Slavs sites dating to the second quarter — the end of the 5th century. The adornment was made of a shell of the genus Murex and is the «legacy» from the Cherniakhіv culture. In the area of that culture are known the pendants made of shells of this genus (type 2 by O. Hopkalo). The pendants from shells appear in use of the Slavs since the second half of the 6th century. Their varieties were used until the first half of the 8th century, although the assemblages and finds with them are few (table 1; fig. 1; 14). In the Slavic assemblages the shells of mollusks of the following species were occurred: Cypraea moneta, C. pantherina, C. tigris, C. arabica. The items from Murex shells are also known. The height of Cypraea moneta is a little more than 2 cm. Other species of shells are larger reaching the height ca. 7—8 cm. The assemblages of the Martinіvka circle include Khatski (fig. 4: A) and Khittsі ones. The grave from Mokhnach belongs to the same antiquities (fig. 2: 2; 5—7). The jewellery by Martynivka circle are dated back to the second half of the 6th century, and the hoards were hidden in the middle — the third quarter of the 7th century. The Pastyrsky circle hoards include the assemblages from Zaitsevo (fig. 4: B) and Kharіvka (fig. 8—10). The hoards by Pastyrsky circle were hidden in the first half of 8th century. The appearance of the pendants from shells is related to the general trend of the spread of Cypraea moneta in Eastern Europe in the early Middle Ages. They are known in the Caucasus, Crimea, the Seversky Donets basin (fig. 11). Cypraea moneta shells were used as pendants in necklaces as evidenced by finds from the Luchiste burial ground from Crimea. The use of other types of shells remains unclear. However, they were probably parts of necklaces or amulets.